Are partner's features important to understand health at older ages? The Spanish case - Jordi Gumà; Jeroen Spijker (Elsevier, 2021)
Objective: To analyse health differences among partnered individuals in Spain aged 65-81 considering their combined (education of both partners and age gap) and household (economic capacity of the household) characteristics. Method: A cross-sectional study of the 2015 Spanish sample of the European Union Statistics on Income and Living Conditions survey (EU-SILC) on partnered individuals aged 65-81 years (N = 1787). Using logistic regression models separately for women and men we obtained odds and predicted probabilities of having less than good health (95% confidence intervals) according to combined information from both partners on education and age, the household's economic capacity and partner's health status. Results: Probabilities of not having good health are significantly less among lower educated women whose partners are more highly educated (compared to both partners being lower educated) and among women whose partner is younger or has good health status. The latter also applies to men. Living in a household without economic difficulties also favours health (both sexes). Conclusions: For both sexes a partner's health status is the variable that shows the largest effect on elderly partnered Spanish people's health but women's health appears to be more sensitive to their partner's educational attainment and the household's economic situation. Resumen: Objetivo: Analizar las diferencias de salud entre la población española de 65 a 81 años de edad que vive en pareja, considerando características individuales, combinadas de ambos miembros y generales de la pareja. Método: Estudio transversal de la muestra española del año 2015 de la Encuesta Europea de Condiciones de Vida de personas mayores (edades 65-81 años) que conviven en pareja (N = 1787). Mediante modelos de regresión logística independientes para mujeres y hombres se obtuvo la estimación de las probabilidades de no tener buena salud autopercibida (intervalos de confianza del 95%) según la combinación del nivel de estudios y la edad de ambos miembros de la pareja, así como la capacidad económica del hogar y el estado de salud del cónyuge. Resultados: Las probabilidades de no tener buena salud son significativamente menores entre las mujeres con menor nivel de educación cuyas parejas son más educadas (en comparación con las que tienen menos educación) y entre las mujeres cuya pareja es más joven o tiene un buen estado de salud. Esto último también se aplica a los hombres. Vivir en un hogar sin dificultades económicas también favorece la salud en ambos sexos. Conclusiones: Para ambos sexos, el estado de salud de la pareja es la variable que muestra el mayor efecto sobre la salud de la población mayor española que vive en pareja, aunque la salud de las mujeres parece ser más sensible al nivel educativo de su pareja y a la situación económica general del hogar.